UNIX for MVS programmers - Singh, Harry (Prentice Hall PTR, 1997)
This book recognizes your strong knowledge base in MVS programming, and shows you how to build on existing skills to master UNIX quickly and easily. UNIX for MVS Programmers addresses the different paradigms of the two operating systems, guiding you through the basics of UNIX and explaining them in comparison to related concepts in MVS. Strengths and weaknesses of the two systems are contrasted, and the history and features of UNIX are introduced.